Keterampilan Supervisor Dalam Peningkatan Kualitas Pembelajaran - Artiana, Artiana (Indonesian Research Journal on Education, 2022)
School supervisors or supervisors are functional officials who are positioned as technical implementers to carry out educational supervision of a certain number of designated or designated schools to improve the quality of learning processes and outcomes/guidance to achieve educational goals. The school supervisor is the main person responsible for the occurrence of school development according to the typeand level. The task is reviewed from the conceptual review of supervision. In supervisory practice, supervisors carry out their functions as supervisors. Supervisors are people who carry out supervision.